Analysis of differences in selected attributes of neuromarketing within socio-demographic characteristic - Anna Tomková; Dagmara Ratnayake-Kaščáková; Ondrijová, Ivana (Technium Social Sciences Journal, 2020)
The aim of the paper is to identify and specify the differences between the assessment of the attributes of neuromarketing and selected socio-demographic characteristics of respondents. The attributes "store information", "seller information" and "product information" were examined in terms of the respondents’ residence and the region of origin of the paticipants. Data were obtained by the questionnaire method according to the Neuromarketing methodology. The established hypotheses were verified on a sample of 190 respondents through statistical analysis in the IBM SPSS statistical program. The analysis did not confirm the existence of statistically significant differences in the perception of the established attributes of neuromarketing in relation to the place of residence (city or countryside). On the contrary, differences were recorded in terms of the region of Slovakia from which the respondent came.